Hydrophobic corrosion-resistant coating and preparation method thereof
By constructing a Cu-Ni-Gr hydrophobic corrosion-resistant coating with a gradient structure on the surface of the titanium alloy, combined with chemical etching and dynamic pulse electrodeposition, the problem of difficult to form a uniform and dense protective layer in the surface treatment of titanium alloy in the prior art is solved. It significantly improves the service life and protection effect of titanium alloy in marine environments.
Patent Information
- Application Number
- CN202411131549.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-19
- Publication Date
- 2024-12-17
AI Technical Summary
The existing titanium alloy surface treatment technology is difficult to form a uniform and dense protective layer in an oxidizing environment, resulting in easy penetration of corrosive media and reducing the service life of titanium alloy.
Cu-Ni-Gr hydrophobic corrosion-resistant coating with gradient structure is constructed on the surface of titanium alloy by chemical etching and dynamic pulse electrodeposition, combining graphene and sulfuric acid. Additives such as sodium improve the mechanical properties and hydrophobicity of the coating.
It significantly improves the bonding strength and corrosion resistance of the coating and substrate, extends the service life of titanium alloy in the marine environment, and enhances the protective effect of the coating.
Smart Images

Figure CN119145022A_ABST
Abstract
Description
Technical field:
[0001] The invention belongs to the technical field of anti-corrosion coatings and relates to a Cu-Ni-Gr hydrophobic anti-corrosion coating with a gradient structure and a preparation method thereof, which can improve the service capability of titanium alloys in marine corrosion environments. Background technology:
[0002] Due to the advantages of titanium alloy such as light weight, low density, high strength, excellent corrosion resistance, heat resistance and low temperature resistance, it is widely used in aerospace, marine engineering, biomedical equipment and other fields. It is an ideal material for manufacturing micro-structures and special functional structures. However, a dense oxide film will form on the surface of titanium alloy in an oxidizing environment. When the oxide film breaks, local corrosion is likely to occur, causing the service life of the titanium alloy to decrease rapidly. At present, the simplest and most efficient way to improve the surface of titanium alloy is surface treatment, including the use of electroplating, chemical etching, anodizing, thermal spraying, physical vapor deposition and other methods to form a new protective layer on the surface of titanium alloy. For example, Chinese patent 202410150854.1 discloses a high-performance titanium alloy coating for use in space environments, including a substrate, which is a Ti-6Al-4V titanium alloy material, on which a chromium bonding layer, a Ti / TiN gradient layer, a main structural layer of TiAlN-CrN alternatingly arranged, and an external functional layer of DLC are sequentially arranged. The preparation method includes the following steps: S1. Surface treatment: The surface of the substrate is subjected to gas etching treatment for 15-25 minutes, and the gas used is argon; S2. The surface-treated substrate is placed in a PVD coating device to prepare a chromium bonding layer, a Ti / TiN gradient layer, and a main structural layer of TiAlN-CrN alternatingly arranged; S3. The substrate is placed in a PECVD coating device to prepare an external functional layer of DLC. Chinese Patent 202311854024.9 discloses a method for preparing a friction-reducing and antibacterial titanium alloy coating, comprising the following steps: preparing a criss-cross elliptical micro-texture on the surface of the titanium alloy, then sequentially performing N ion implantation and Cu ion implantation, and chemically plating copper on the surface of the titanium alloy after the ion implantation, to finally obtain a friction-reducing and antibacterial titanium alloy coating. Chinese Patent 202311810831.0 discloses a wear-resistant and friction-reducing titanium alloy coating, which is composed of a matrix phase, a reinforcement phase and a lubricating phase, wherein the matrix phase is a titanium alloy; the lubricating phase is one of silver, hexagonal boron nitride and barium fluoride; the reinforcement phase is a combination of cubic boron nitride ceramic particles and a hard phase; the hard phase is TiN, TiB and Ti2Ni, and the preparation method comprises the following steps:
[0003] S1, after mixing the matrix phase raw material and the lubricating phase raw material in proportion, ball milling is performed to obtain a composite powder; S2, after the composite powder and the reinforcing phase raw material are proportioned in proportion, mechanical mixing is performed to obtain a mixed powder; S3, the mixed powder is clad on the surface of the titanium alloy substrate by high-speed laser to prepare a wear-resistant and friction-reducing titanium alloy coating. Chinese patent 202211616257.0 discloses a wear-resistant and corrosion-resistant titanium alloy coating, the raw materials for preparation include titanium alloy powder, and the content of each element in the titanium alloy powder by mass percentage is: Al: 5.5% to 6.75%; V: 3.5% to 4.5%; Fe: ≤0.03%%; C: ≤0.08%%; O: ≤0.20%; N: ≤0.05%; H: ≤0.015%; the remainder is Ti and impurity elements, and the preparation method is: in an inert atmosphere environment, the titanium alloy powder is used to scan the surface of the substrate by laser cladding. Among them, the coating obtained by the physical vapor deposition method has a weak bonding force with the substrate, and it is easy to produce holes and gaps; the coating obtained by the thermal spraying method has a large surface roughness, and it is easy to form holes on the surface, so that the corrosive medium can easily penetrate the coating and corrode the substrate; although the anodic oxidation method can obtain a wear-resistant and corrosion-resistant oxide film, the oxide film is brittle and porous, and it is difficult to obtain a uniform oxide film. The electrochemical deposition method is a classic surface coating technology, mainly including direct current electrodeposition and pulse electrodeposition. Its principle is to reduce the metal cations in the salt solution in the electroplating solution into metal elements and deposit them on the surface of the cathode substrate to form a coating of a certain thickness. The quality of the coating is closely related to the electrodeposition process parameters. The direct current electrodeposition method is a commonly used and earliest method for preparing composite coatings. It has the advantages of simple instruments and equipment, simple experimental operation, and low cost. The prepared nickel-based composite coating has a bright surface, uniform structure, and good performance. However, the prepared composite coating has coarse grains and is prone to defects such as cracks and pores. Compared with direct current electrodeposition, pulse electrodeposition uses pulse power instead of direct current for electroplating. By controlling parameters such as waveform, frequency, on-off ratio and average current density, the electrodeposition process can be changed in a wide range, and a coating with certain characteristics can be obtained in a certain plating solution, thereby forming a more uniform and dense composite coating. Therefore, pulse electrodeposition has the following advantages: (1) the coating structure is changed, the grain size is small, and a dense and uniformly bright coating can be obtained; (2) the dispersion ability and deep plating ability are improved, which is conducive to the co-deposition of non-metallic materials; (3) the coating has low porosity and improved corrosion resistance; (4) the internal stress of the coating is reduced and the toughness of the coating is improved; (5) the wear resistance of the coating is improved; (6) the impurity content in the coating is reduced; (7) a composite coating with stable composition can be obtained. Chemical etching is a simple and efficient surface treatment method. The principle is to use a solution with a certain corrosiveness to react chemically with the substance on the surface of the substrate to achieve the result of etching the surface, in order to construct a rough micron structure on the surface and improve the bonding strength between the coating and the substrate.Through chemical etching and pulse electrodeposition, it is expected to prepare a uniform, dense and well-bonded coating on the surface of titanium alloy.
[0004] The composition and structural design of the coating are crucial to improving its ability to protect the substrate. In terms of composition design, adding corrosion-resistant metal or non-metallic elements to the Cu coating is expected to further improve the corrosion resistance of copper and improve the mechanical properties of copper. In terms of structural design, functional gradient materials are obtained by using special preparation methods to make the composition, structure, porosity and other elements of the material continuously change along the thickness direction, thereby obtaining non-homogeneous materials whose physical, chemical and other properties also change continuously in a gradient. Among them, the strategy of "top-down" or "bottom-up" gradient distribution of grain size has been widely studied to customize the performance of materials: the grain size is reduced from coarse grains in the core to nano-scale grains on the surface, which can give metals and alloys high strength and hardness without sacrificing too much ductility, solving the "seesaw" problem of strength and plasticity of traditional metal and alloy materials. Therefore, the research and development of a hydrophobic anti-corrosion coating and its preparation method, and the application of the gradient structure in the coating system are expected to give the coating surface excellent mechanical properties while ensuring the bonding between the coating and the substrate. Summary of the invention:
[0005] The purpose of the present invention is to overcome the shortcomings of the prior art, develop and design a Cu-Ni-Gr hydrophobic anti-corrosion coating with a gradient structure and a preparation method thereof, so that the coating surface has better mechanical properties and the coating and the substrate have good bonding strength.
[0006] In order to achieve the above-mentioned purpose, the present invention relates to a hydrophobic anti-corrosion coating with good corrosion resistance, hydrophobicity and mechanical properties, a bonding force with a substrate of not less than 15N, a corrosion potential of -185mV, an optimal hydrophobic angle of 156°, components including Cu, Ni and Gr, a coating grain size with a gradient distribution, gradually decreasing from bottom to top, which is achieved by controlling the average current density during the electrodeposition process, and is applied to the surface of marine transportation machinery to improve the service life of titanium alloys in marine service environments; wherein the molar mass fractions of Cu, Ni and Gr are 80-90%, 10-20% and 0.5-3%, respectively.
[0007] The process of a method for preparing a hydrophobic anti-corrosion coating according to the present invention is as follows:
[0008] First, a micro-nano structure is constructed on the substrate surface;
[0009] Then, an electroplating solution is prepared using copper sulfate, nickel sulfate, sodium sulfate, graphene and additives;
[0010] Finally, the substrate is placed in an electroplating solution to prepare a hydrophobic anti-corrosion coating on the surface of the substrate.
[0011] Specifically:
[0012] Firstly, a rough micro-nano structure is constructed on the substrate surface by chemical etching using an etching medium;
[0013] The etching medium includes hydrofluoric acid and nitric acid, with mass fractions of 10-20% and 30-50% respectively;
[0014] Then, copper sulfate, nickel sulfate, sodium sulfate, graphene and additives are mixed and ultrasonicated for 30 minutes to make them uniformly mixed to prepare an electroplating solution, and the pH value of the electroplating solution is adjusted to 1-2 by dilute sulfuric acid or sodium hydroxide aqueous solution;
[0015] Wherein, copper sulfate is copper sulfate pentahydrate with a concentration of 120-180 g / L, nickel sulfate has a concentration of 60-100 g / L, sodium sulfate is sodium dodecyl sulfate with a concentration of 1-2 g / L, graphene has a concentration of 0.05-2 g / L, additives include gelatin with a concentration of 5-15 mg / L, and the balance is deionized water;
[0016] Finally, the substrate is placed in an electroplating solution, and a hydrophobic anti-corrosion coating is deposited on the surface of the substrate by a dynamic pulse electrodeposition method;
[0017] The parameters of dynamic pulse electrodeposition are as follows: duty cycle is 40-60%, forward electroplating time is 20ms, reverse electroplating time is 1-5ms, and average current density is 60-300mA / cm 2 , temperature is 35-55℃, and inter-electrode distance is 20-50mm.
[0018] The invention relates to a method for preparing a hydrophobic anti-corrosion coating, which controls the dynamic pulse electrodeposition process parameters so that the grain size of the coating gradually decreases from the substrate to the top, and promotes the coating surface to have better mechanical properties through the gradient structure, thereby increasing the bonding strength between the coating and the substrate.
[0019] Compared with the prior art, the present invention sequentially performs chemical etching and pulse electrodeposition on the surface of a titanium alloy substrate to obtain a "top-down" gradient nanostructure, a gradient structural change that gradually transitions from the surface to the bottom, from fine crystals to coarse crystals and then to nanocrystals, and a gradient continuous change in physical properties; the graphene added to the electroplating solution can make the coating structure more complete and evenly distributed, inhibit the growth of grains, refine the grains, and the graphene is distributed at the grain boundaries, hindering the dislocation movement and the penetration of water molecules, thereby improving the mechanical properties and hydrophobic properties of the coating; the sodium sulfate and additives added to the electroplating solution can significantly improve the dispersion ability of the graphene in the electroplating solution, and avoid the agglomeration of the graphene during the electrodeposition process; the prepared coating has a bright surface, a uniform and dense structure, not only has good hydrophobic and corrosion resistance, but also has improved mechanical properties, further extending the protective life of the coating. Description of the drawings:
[0020] Figure 1 It is a schematic diagram of the gradient structure of the hydrophobic anti-corrosion coating involved in the present invention.
[0021] Figure 2 It is a schematic diagram of the substrate and the hydrophobic anti-corrosion coating involved in the present invention, wherein the titanium alloy substrate is the substrate and the copper-nickel graphene composite coating is the hydrophobic anti-corrosion coating.
[0022] Figure 3 It is a schematic diagram of the contact angle of the hydrophobic anti-corrosion coating according to the present invention.
[0023] Figure 4 This is a surface morphology diagram of the hydrophobic anti-corrosion coating involved in Example 2 of the present invention. Specific implementation method:
[0024] The present invention will be further described below in conjunction with the accompanying drawings and specific embodiments.
[0025] The specific process engineering of a method for preparing a hydrophobic anti-corrosion coating involved in this embodiment includes the following steps:
[0026] S1. Substrate treatment
[0027] The TC4 titanium alloy substrate was polished with sandpaper, and then immersed in acetone for ultrasonic-assisted chemical degreasing for 8 minutes, and then immersed in anhydrous ethanol and deionized water for ultrasonic-assisted cleaning for 3 minutes respectively, and then dried for later use;
[0028] S2. Prepare chemical etching solution
[0029] A chemical etching solution is prepared by using hydrofluoric acid, nitric acid, deionized water and disodium ethylenediaminetetraacetate, wherein the mass fraction of hydrofluoric acid is 10%, the mass fraction of nitric acid is 30%, the mass fraction of deionized water is 60%, and the concentration of disodium ethylenediaminetetraacetate is 1 g / L;
[0030] The concentration of hydrofluoric acid is 40%, the concentration of nitric acid is 65-68%, and disodium ethylenediaminetetraacetic acid can improve the durability of chemical etching solution;
[0031] S3, chemical etching
[0032] The substrate was placed in a chemical etching solution and uniformly etched at a constant temperature of 25°C. After 2 minutes, the substrate surface was cleaned with a strong alkaline solution, then rinsed with deionized water, and dried.
[0033] S4. Prepare the plating solution
[0034] The electroplating solution is prepared by using copper sulfate pentahydrate, nickel sulfate, sodium dodecyl sulfate, graphene, gelatin and deionized water, and ultrasonic treatment is performed for 30 minutes to ensure uniformity. The pH value of the electroplating solution is adjusted to 1.5 by using 10% by volume of dilute sulfuric acid or 5% by mass of sodium hydroxide aqueous solution, wherein the concentration of copper sulfate pentahydrate is 150 g / L, the concentration of nickel sulfate is 80 g / L, the concentration of sodium dodecyl sulfate is 1.4 g / L, the concentration of graphene is 0.4 g / L, the concentration of gelatin is 8 mg / L, and the balance is deionized water;
[0035] S5. Electroplating
[0036] An electrolytic copper-nickel alloy plate with a purity of 99.99% is used as an anode, and a substrate obtained by the treatment in step S3 is used as a cathode. A power source is connected, and an electroplating tank containing an electroplating solution is placed in a constant temperature water bath. The substrate is placed in the electroplating solution to deposit a Cu-Ni-Gr anti-corrosion hydrophobic coating with a gradient structure on the surface of the substrate through a dynamic pulse electroplating process. The electroplating process is always accompanied by stirring. The parameters of the dynamic pulse electroplating are as follows: a duty cycle of 40-60%, a forward electroplating time of 20 ms in a single cycle, a reverse electroplating time of 1-5 ms, and an average current density of 60-300 mA / cm 2 , temperature is 35-55℃, and inter-electrode distance is 20-50mm.
[0037] The present embodiment involves a method for preparing a hydrophobic and anti-corrosion coating, which prepares a Cu-Ni-Gr anti-corrosion and hydrophobic coating with a gradient structure on the surface of a titanium alloy substrate by chemical etching + dynamic pulse electrodeposition, thereby improving the service capability of the titanium alloy in a marine environment. The addition of Ni and graphene can significantly improve the corrosion resistance of the Cu coating.
[0038] Embodiment 1:
[0039] The specific process of the method for preparing a hydrophobic anti-corrosion coating involved in this embodiment is the same as that in embodiment 1, except that the parameters of the dynamic pulse electrodeposition are as follows: the duty cycle is 40%, the forward electroplating time in a single cycle is 20 ms, the reverse electroplating time is 1 ms, the current density changes arithmetic difference every 10 minutes, and the total change is (60 mA / cm 2 →140mA / cm 2 ), the temperature was 35°C, the inter-electrode distance was 50 mm, and after pulse electroplating for 40 min, it was cleaned by an ultrasonic cleaner and placed in a blast drying oven at a temperature of 80°C for 6 h;
[0040] The surface morphology was observed by scanning electron microscopy, which showed that the surface was relatively uniform and had good density. Further observation of the cross-sectional characteristics showed that the thickness of the coating was about 32 μm.
[0041] The film-based bonding strength between the coating and the substrate tested by the scratch tester is about 15.8N;
[0042] The contact angle measured by a contact angle meter was 142°, indicating hydrophobicity;
[0043] The corrosion potential measured by the electrochemical workstation was -201 mV.
[0044] Embodiment 2:
[0045] The specific process of the method for preparing a hydrophobic anti-corrosion coating involved in this embodiment is the same as that in embodiment 1, except that the parameters of the dynamic pulse electrodeposition are as follows: the duty cycle is 50%, the forward electroplating time in a single cycle is 20 ms, the reverse electroplating time is 2 ms, the current density changes arithmetic difference every 10 minutes, and the total change is (60 mA / cm 2 →220mA / cm 2 ), the temperature is 45°C, the inter-electrode distance is 35 mm, after pulse electroplating for 40 min, it is cleaned by an ultrasonic cleaner and placed in a blast drying oven at a temperature of 80°C for 6 h;
[0046] The surface morphology was observed by scanning electron microscopy, which showed that the surface was uniform and dense, with no obvious abnormal enlargement of pores and particles. Further observation of the cross-sectional characteristics showed that the thickness of the coating was about 42 μm.
[0047] The film-based bonding strength between the coating and the substrate tested by the scratch tester is about 21.8N;
[0048] The contact angle measured by a contact angle meter was 156°, indicating hydrophobicity;
[0049] The corrosion potential measured by the electrochemical workstation was -185 mV.
[0050] Embodiment 3:
[0051] The specific process of the method for preparing a hydrophobic anti-corrosion coating involved in this embodiment is the same as that in embodiment 1, except that the parameters of the dynamic pulse electrodeposition are as follows: the duty cycle is 50%, the forward electroplating time in a single cycle is 20 ms, the reverse electroplating time is 5 ms, the current density changes arithmetic every 10 minutes, and the total change is (60 mA / cm 2 →300mA / cm 2 ), the temperature was 55°C, the inter-electrode distance was 20 mm, and after pulse electroplating for 40 min, it was cleaned by an ultrasonic cleaner and placed in a blast drying oven at a temperature of 80°C for 6 h;
[0052] The surface morphology was observed by scanning electron microscopy, which showed that the surface was uniform, the particles were relatively coarse, and there were no obvious pores. Further observation of the cross-sectional characteristics showed that the thickness of the coating was about 53 μm.
[0053] The film-based bonding strength between the coating and the substrate tested by the scratch tester is about 18.8N;
[0054] The contact angle measured by a contact angle meter was 149°, indicating hydrophobicity;
[0055] The corrosion potential measured by the electrochemical workstation was -193 mV.
[0056] Comparative Example 1:
[0057] In this embodiment, the titanium alloy substrate after chemical etching is used as the cathode and the copper-nickel alloy plate is used as the anode. The substrate and the copper-nickel alloy plate are placed in the electroplating solution for electroplating to prepare the Cu-Ni-Gr coating. The electroplating process is always accompanied by stirring. The parameters of dynamic pulse electrodeposition are as follows: the duty cycle is 50%, the forward electroplating time in a single cycle is 20ms, the reverse electroplating time is 2ms, and the constant current density is 140mA / cm 2 , the temperature is 45℃, the inter-electrode distance is 35mm, after pulse plating for 40min, it is cleaned by ultrasonic cleaning machine and placed in a blast drying oven at 80℃ for 6h;
[0058] The surface morphology was observed using a scanning electron microscope, which showed that the surface was uniform, the particles were relatively coarse, and there were certain pores. Further observation of the cross-sectional characteristics showed that the coating thickness was about 38 μm.
[0059] The film-base bonding strength between the coating and the substrate tested by the scratch tester is about 14.1N;
[0060] The contact angle measured by the contact angle meter was 125°, indicating poor hydrophobicity;
[0061] The corrosion potential measured by the electrochemical workstation was -228 mV, indicating that surface defects led to a decrease in corrosion resistance.
[0062] Comparative Example 2:
[0063] In this embodiment, the titanium alloy substrate after chemical etching is used as the cathode, and the copper-nickel alloy plate is used as the anode. The substrate and the copper-nickel alloy plate are placed in the electroplating solution for electroplating to prepare the Cu-Ni-Gr coating. The electroplating process is always accompanied by stirring. The parameters of the direct current deposition are as follows: the constant current density is 140mA / cm 2 , the temperature is 45℃, the inter-electrode distance is 35mm, after pulse plating for 40min, it is cleaned by ultrasonic cleaning machine and placed in a blast drying oven at 80℃ for 6h;
[0064] The surface morphology was observed using a scanning electron microscope, which showed that the surface particles were coarse and there were certain pores. Further observation of the cross-sectional characteristics showed that the coating thickness was about 48 μm.
[0065] The film-base bonding strength between the coating and the substrate tested by the scratch tester is about 12.6N;
[0066] The contact angle measured by the contact angle meter was 118°, indicating poor hydrophobicity;
[0067] The corrosion potential measured by the electrochemical workstation was -235 mV, indicating that surface defects led to a decrease in corrosion resistance.
[0068] The test parameters of Examples 2-4 and Comparative Examples 1-2 are summarized as follows:
[0069]
[0070]
[0071] In order to conduct intuitive comparative analysis.
Claims
1. A hydrophobic anti-corrosion coating, characterized in that: The components include Cu, Ni and Gr, and the grain size is distributed in a gradient, decreasing from bottom to top.
2. The hydrophobic anti-corrosion coating according to claim 1, characterized in that: The bonding force with the substrate is no less than 15N, the corrosion potential is -185mV, and the optimal hydrophobic angle is 156°.
3. The hydrophobic anti-corrosion coating according to claim 1 or 2, characterized in that: The molar mass fractions of Cu, Ni and Gr are 80-90%, 10-20% and 0.5-3% respectively.
4. A method for preparing a hydrophobic anti-corrosion coating, characterized in that: The process is: First, a micro-nano structure is constructed on the substrate surface; Then, an electroplating solution is prepared using copper sulfate, nickel sulfate, sodium sulfate, graphene and additives; Finally, the substrate is placed in an electroplating solution to prepare a hydrophobic anti-corrosion coating on the surface of the substrate.
5. The method for preparing a hydrophobic anti-corrosion coating according to claim 4, characterized in that: The specific process is: Firstly, an etching medium is used to construct a micro-nano structure on the substrate surface by chemical etching; Then, copper sulfate, nickel sulfate, sodium sulfate, graphene and additives are mixed and ultrasonicated for 30 minutes to prepare an electroplating solution, and the pH value of the electroplating solution is adjusted to 1-2; Finally, the substrate is placed in an electroplating solution, and a hydrophobic anti-corrosion coating is deposited on the surface of the substrate by a dynamic pulse electrodeposition method.
6. The hydrophobic anti-corrosion coating according to claim 5, characterized in that: The etching medium includes hydrofluoric acid and nitric acid, with mass fractions of 10-20% and 30-50% respectively.
7. The hydrophobic anti-corrosion coating according to claim 5, characterized in that: The copper sulfate is copper sulfate pentahydrate with a concentration of 120-180 g / L, the nickel sulfate has a concentration of 60-100 g / L, the sodium sulfate is sodium dodecyl sulfate with a concentration of 1-2 g / L, the graphene has a concentration of 0.05-2 g / L, the additives include gelatin with a concentration of 5-15 mg / L, and the balance is deionized water.
8. The hydrophobic anti-corrosion coating according to claim 5, characterized in that: Dynamic pulse electrodeposition parameters: duty cycle 40-60%, forward plating time 20ms, reverse plating time 1-5ms, average current density 60-300mA / cm 2 , temperature is 35-55℃, and inter-electrode distance is 20-50mm.
9. The method for preparing a hydrophobic anti-corrosion coating according to any one of claims 5 to 8, characterized in that: By controlling the dynamic pulse electrodeposition process parameters, the grain size of the coating gradually decreases from the substrate to the top. The gradient structure can improve the mechanical properties of the coating surface and increase the bonding strength between the coating and the substrate.
Citation Information
Patent Citations
Wear-resistant and corrosion-resistant titanium alloy coating and preparation method thereof
CN115976506A
Wear-resistant antifriction titanium alloy coating and preparation method thereof
CN117821962A
Antifriction antibacterial titanium alloy coating as well as preparation method and application thereof
CN117904613A
High-performance titanium alloy coating applied to space environment and preparation method of high-performance titanium alloy coating
CN118086901A
